An investigation of the antibacterial activity of Palo-China (Cassia alata). - Venturanza, Katte Rea N. (2009.)
The crude methanolic extract of palo-china leaves were found to be highly active against Staphylococcus aureus by paper disc diffusion assay., Preliminary screening for alkaloids and saponins in Palo-china leaves gave negative results for both tests. Sequential liquid-liquid extraction was employed to separate the crude methanolic extract into four fractions; namely, hexane, dichloromethane (DCM), ethyl acetate, and aqueous portions. To identify the fraction to which the antibacterial activity of the Palo-china leaves may be attributed, the three organic extracts and the aqueous portion was tested against S. aureus. Thin-layer chromatography screening was performed on the crude methanolic extract and the four fractions. using spray reagents, the crude extract tested positive for phenols, tannins, flavonoids, triterpenes, sterols, and essential oils. The DCM extract was found to be active against the test organism. Its activity was found to be significantly different compared to the two other organic extracts. Also, the TLC profile of the said fraction was the closest match to the crude sample in terms of complexity and Rf values. It can be inferred that the antibacterial activity of Palo-china leaves is due largely to the DCM extract; and thus, the constituent responsible for the bioactivityis semi-polar in nature.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Palo-China.; Cassia Alata L